Services sector in the Caribbean economies : some development and management issues - Charles, Sylvia (ISER Cave HillBB, 1994)
Examines the services sectors of eleven English-speaking Caribbean countries. Presents an outline of the pattern of development in world services in terms of output, employment and trade. Highlights some development and management issues against the background of the statistical findings and in relation to international demand trends.